90-(5x+10)=90-(x+2)

Simple and best practice solution for 90-(5x+10)=90-(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90-(5x+10)=90-(x+2) equation:


Simplifying
90 + -1(5x + 10) = 90 + -1(x + 2)

Reorder the terms:
90 + -1(10 + 5x) = 90 + -1(x + 2)
90 + (10 * -1 + 5x * -1) = 90 + -1(x + 2)
90 + (-10 + -5x) = 90 + -1(x + 2)

Combine like terms: 90 + -10 = 80
80 + -5x = 90 + -1(x + 2)

Reorder the terms:
80 + -5x = 90 + -1(2 + x)
80 + -5x = 90 + (2 * -1 + x * -1)
80 + -5x = 90 + (-2 + -1x)

Combine like terms: 90 + -2 = 88
80 + -5x = 88 + -1x

Solving
80 + -5x = 88 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
80 + -5x + x = 88 + -1x + x

Combine like terms: -5x + x = -4x
80 + -4x = 88 + -1x + x

Combine like terms: -1x + x = 0
80 + -4x = 88 + 0
80 + -4x = 88

Add '-80' to each side of the equation.
80 + -80 + -4x = 88 + -80

Combine like terms: 80 + -80 = 0
0 + -4x = 88 + -80
-4x = 88 + -80

Combine like terms: 88 + -80 = 8
-4x = 8

Divide each side by '-4'.
x = -2

Simplifying
x = -2

See similar equations:

| 5x^2+x-10=0 | | 63-3x=11-9x | | 0x+11=71-3x | | 5x-94=2x-7 | | 4x-8-2x=x-2 | | 5(4-3)=19 | | 2(5-4)=2 | | 6x+2x^2+1=1 | | 2(30-12)=18 | | 4a^2+625b^4=0 | | 4n+55=8 | | x^4-4x^2+1=0 | | 26=6 | | 14-10x=36-24x | | 8x^4+28x^3-30x^2+11x-2=0 | | 3(6x-14)=12x+6(x-3) | | 1x+10=91+x | | 3(15+2x)-60+9x=0 | | 1.875x+2.125y=97.1 | | 2x+1/3=17 | | 2x+4d+6x-5c+4f= | | (x^2+x)(x+6)=7x | | 10x+30=8x+20 | | 2y-30=0 | | y=400+.25(0) | | y=400+.25(-1600) | | ln(5x-9)=1 | | 106-4x=14x+20 | | 228781=1010x-x^2 | | 5-7X=122-28X | | 1096x-x^2=268975 | | 78-2x=25x+18 |

Equations solver categories